Assessment of Medication Adherence to JNC-7 Guidelines and Risk Factors for Hypertension in a South Indian Tertiary Care Hospital - Narra, Uday Bhaskar; Pingili, Ravindrababu; Chinnam, Sri Varsha Reddy; Datla, Prardhana Devi; Potluri, Sree Varsha; Kilaru, Naveen Babu (Indian Journal of Pharmacy Practice)
Objective: The objective of the study was to assess the drug utilization pattern, medication adherence to Joint National Committee (JNC-7) treatment guidelines and risk factors for hypertension (HTN) in a south Indian tertiary care teaching hospital. Methods: A prospective study was conducted on 1000 subjects (with or without hypertension) from November 2015 to April 2016 in a general medicine department. Drug utilization pattern, medication adherence was assessed by comparing with the JNC-7 guidelines and the odds ratios were calculated in univariate regression analysis for risk factors. Results: Stage 1 hypertension (47.30%) was most predominant than stage 2 hypertension (24.28%) and hypertension emergency (12.23%) according to the SBP of JNC-7 guidelines. Hypertension was significantly higher in the subjects of age above 40 years (92.6%, P<0.0001), married (99.6%, P<0.0001), educated (59.5%, P=0.066), known family history (father, P=0.009; mother, P<0.0001; father and mother, P<0.0001), physical inactivity (74.8%, P<0.001), monthly income above Rs. 10,000 (34.5%, P<0.0001), co-morbidities (diabetes, P<0.0001; history of cardiovascular diseases, P<0.0001; chronic kidney disease, P<0.0001), alcohol consumption (19.2%, P=0.007), smoking (23%, P=0.0005), tea consumption (twice or more per day, P=0.027), and intake of junk foods (thrice or more in a week, P<0.0001) than normotensive subjects. Angiotensin receptor blockers (17.98%) are most widely prescribed drugs followed by calcium channel blockers (10.07%) and ß-blockers (6.29%) in monotherapy (38.63%). Angiotensin receptor blocker + diuretic combination (24.64%) was mostly used in two drug combination therapy (36.11%). The overall rate of adherence was 24.9% (Pre hypertension, P<0.01); 80.3% (Stage 1 hypertension, P<0.001); 73.93% (Stage 2 hypertension, P<0.001) and 50% (Hypertension emergency, P<0.05). Univariate regression analysis showed that age (above 40 years), female gender, married, widowed, generalized obesity, moderate to high economic status (Above 10, 000/month), family history, diabetes, history of cardiovascular diseases, chronic kidney disease, physical inactivity, smoking, alcohol consumption and junk food (weekly thrice or more, odds ratio: 17.69, 95% confidence interval: 2.373-131.8, P<0.0001) intake were significantly associated with HTN. Conclusion: The present study results suggested that medication adherence to JNC-7 was optimal. Junk foods, age (above 60 years), diabetes, alcohol, smoking, marital status and high economic status are the main risk factors for hypertension.
Keywords: Odds Ratio; Hypertension; Risk Factors; Medication Adherence; Junk Foods; JNC-7